2015
DOI: 10.1080/10408398.2015.1077195
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, an active component of turmeric (Curcuma longa), and its effects on health

Abstract: Turmeric (Curcuma longa) is a type of herb belonging to ginger family, which is widely grown in southern and south western tropical Asia region. Turmeric, which has an importance place in the cuisines of Iran, Malesia, India, China, Polynesia, and Thailand, is often used as spice and has an effect on the nature, color, and taste of foods. Turmeric is also known to have been used for centuries in India and China for the medical treatments of illnesses such as dermatologic diseases, infection, stress, and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
536
0
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 926 publications
(635 citation statements)
references
References 61 publications
2
536
0
20
Order By: Relevance
“…These health benign effects of turmeric can be exhibited because of its essential oils and phenolic component‐rich bioactive compounds. Among the bioactive compounds of turmeric; curcuminoids are the most popular phenolic component because it provides maximum biological activity (Kocaadam & Sanlier, ). But, unstable and hydrophobic nature of pure curcuminoids limits its use in the biological system.…”
Section: Introductionmentioning
confidence: 99%
“…These health benign effects of turmeric can be exhibited because of its essential oils and phenolic component‐rich bioactive compounds. Among the bioactive compounds of turmeric; curcuminoids are the most popular phenolic component because it provides maximum biological activity (Kocaadam & Sanlier, ). But, unstable and hydrophobic nature of pure curcuminoids limits its use in the biological system.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a natural polyphenol present in turmeric that possess many biological activities, including anti-infectious, anti-inflammatory, anti-oxidant and chemopreventive effects (10). Recent studies have shown that curcumin is able to inhibit the proliferation, invasion and metastasis of a variety of tumor cells (10,11). Multiple cellular signaling pathways have been proven to be regulated by curcumin in cancer treatment including mitogen-activated protein kinase (MAPK), nuclear factor-κB (NF-κB), Akt, Wnt/β-catenin and others (10).…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric is widely used in cooking, medicine, beauty, and health products. [267][268][269][270][271][272][273] Turmeric as a crude extract or tuber powder normally used for skin care among South Indian women in their daily routine owing to its multibeneficial activities such as antiaging, moisture retention, antioxidant activity, and natural beauty products with yellow pigments. [274][275][276][277][278][279][280][281] Although turmeric has multiple beneficial activities, its bright yellow color and instability under certain environmental conditions make researchers look for alternative delivery technologies for skin care and beauty applications.…”
Section: Nanocurcuminmentioning
confidence: 99%